Reflections on the Dismissal of Theft Charges Through Prosecutor's Restorative Justice House in Lampung - Kusworo, Daffa Ladro; Abdulkadir, Abdulrazaq Owolabi; Fauzi, Maghfira Nur Khaliza (Jurnal Media Hukum, 2000)
The existence of restorative justice certainly brings a new paradigm in the settlement of criminal cases by seeking to resolve cases solely outside of court. The implementation of restorative justice-based prosecution termination can be applied to theft, which has the highest number of cases in Indonesia. This is because the Covid-19 pandemic created a moral crisis that led to a drastic increase in theft crimes in Indonesia, disrupting economic stability. Recently, restorative justice houses have been established in each jurisdiction of the prosecutor's office to optimize the resolution of legal problems by filtering cases that go to court, disseminating law to local residents, and involving local traditional leaders to develop local wisdom and emphasize consensus deliberation. The research approach used a normative juridical method, referencing laws and regulations sourced from primary data and literature studies on criminal law in Indonesia, which were then processed to draw specific conclusions. The study's results show that humanist restorative justice houses are an alternative for solving theft cases. The embodiment of restorative justice in a hybrid way within the prosecutor's office will establish it as a humane law enforcement agency in Lampung province.